Genetic association of productive traits, carcass measurements and age at first calving in the genetic evaluation of the Nellore breed - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C. I. Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
The aim was to evaluate the genetic association between sexual precocity and productive performance in Nellore cattle. Records of standardized body weights at 120 (W120), 210 (W210), 365 (W365), and 450 (W450) days of age, Longissimus Muscle Area (LMA), backfat thickness (BFT), and age at first calving (AFC) were used. The mixed linear model included the fixed effects of contemporary groups (composed of herd, year, and season of birth, as well as the animal’s sex), in addition to the random effects of direct additive genetic, maternal genetic (for W120 and W210), and maternal permanent environment. The variance components were estimated by the restricted maximum likelihood method. The obtained direct heritability estimates were 0.45, 0.49, 0.42, 0.40, 0.33, 0.19, and 0.08 for W120, W210, W365, W450, LMA, BFT, and AFC, respectively. The Spearman correlations of the animals’ breeding values between the weight development estimates were of a high order, and for the traits of backfat thickness and age at first calving, it was 0.27, indicating a relationship at older ages with the onset of the acceleration of adipogenesis. The genetic gain obtained in AFC (0.48 days) with the correlated response related to LMA and BFT was − 0.05 and − 0.19 days, respectively. The genetic correlations obtained between AFC and the weight development traits were positive, however negative with the carcass-associated traits, indicating that the offspring are reproductively precocious, yet lighter and with a greater finish of subcutaneous fat.

Reaction norm models for the evaluation of reproductive and productive performance in Nellore cattle - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C.I Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
This study evaluated genotype × environment interactions (G×E) in Nellore cattle for growth, reproductive, and carcass traits using reaction norm models. We analyzed the records of body weight and scrotal circumference at 12 and 18 months. (W365, W450, SC365, SC450), as well as loin eye area (LEA) and subcutaneous fat thickness (SFT), from herds across different Brazilian states were analyzed. A hierarchical one-step reaction norm model was applied, including fixed effects of contemporary groups (herd, year and season of birth, and sex), cow age at calving as a covariate, and random effects for additive genetics, permanent environment, and residuals. Bayesian inference with Gibbs sampling was used to estimate posterior distributions.Sires were classified according to environmental sensitivity into four categories: extremely robust, robust, plastic, and extremely plastic. For most traits, over 90% of sires were classified as robust or extremely robust, indicating stability of ranking across environments. Exceptions were observed for SFT and SC365, where lower correlations between extreme environmental gradients suggested G×E effects. Heritability estimates ranged from 0.07 to 0.32 for body weights and reached up to 0.76 for fat thickness, with higher values observed under more favorable environmental conditions. .These findings underscore the utility of reaction norm models for identifying environmentally robust sires under the variability of tropical production systems, thereby supporting more accurate and efficient selection decisions in genetic improvement programs.

Climate change impacts on the potential global distribution of Maconellicoccus hirsutus - Iro A. Georgopoulou; Dimitrios P. Papachristos; Panagiotis G. Milonas; Sonia Alkafy Baldi; Darren J. Kriticos (Biological Invasions, 2025)

Exploring novel circulating biomarkers for liver cancer through extracellular vesicle characterization with infrared spectroscopy and plasmonics - R. Di Santo; F. Verdelli; B. Niccolini; S. Varca; A. del Gaudio; F. Di Giacinto; M. De Spirito; M. Pea; E. Giovine; A. Notargiacomo; M. Ortolani; A. Di Gaspare; et al. (Analytica Chimica Acta, 2024)

Estimating genetic parameters of reproductive, carcass, and meat quality traits in Polled Nellore cattle - M. M. S. Mamede; G. J. M. Rosa; E. C. Eifert; F. B. Lopes; F. Baldi; M. F. Costa; R. D. Sainz; A. S. Carmo; A. S. Mascioli; C. U. Magnabosco (Tropical Animal Health and Production, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Stealth invasions on the rise: rapid long-distance establishment of exotic pines in mountain grasslands of Argentina - Tomás Milani; Esteban G. Jobbágy; Martín A. Nuñez; M. Eugenia Ferrero; Germán Baldi; François P. Teste (Biological Invasions, 2020)

Social-Ecological Functional Types: Connecting People and Ecosystems in the Argentine Chaco - M. Vallejos; S. Aguiar; G. Baldi; M. E. Mastrángelo; F. Gallego; M. Pacheco-Romero; D. Alcaraz-Segura; J. M. Paruelo (Ecosystems, 2020)

Genetic association between temperament and sexual precocity indicator traits in Nellore cattle - T. S. Valente; A. C. Sant’Anna; F. Baldi; L. G. Albuquerque; Mateus J. R. Paranhos da Costa (Journal of Applied Genetics, 2015)

Genetic parameters and investigation of genotype × environment interactions in Nellore × Hereford crossbred for resistance to cattle ticks in different regions of Brazil - D. R. Ayres; R. J. Pereira; A. A. Boligon; F. Baldi; V. M. Roso; L. G. Albuquerque (Journal of Applied Genetics, 2015)

Computer image analysis: an additional tool for the identification of processed poultry and mammal protein containing bones - L. Pinotti; T. Fearn; S. Gulalp; A. Campagnoli; M. Ottoboni; A. Baldi; F. Cheli; G. Savoini; V. Dell’Orto (Food Additives & Contaminants: Part A, 2013)

The imprint of humans on landscape patterns and vegetation functioning in the dry subtropics - Germán Baldi; Santiago R. Verón; Esteban G. Jobbágy (Global Change Biology, 2013)
Dry subtropical regions (DST), originally hosting woodlands and savannas, are subject to contrasting human pressures and land uses and different degrees of water limitation. We quantified how this variable context influences landscape pattern and vegetation functioning, by exploring the associations between three groups of variables describing (i) human pressures (population density, poverty, and market isolation) and climate (water availability), (ii) landscape pattern (woody cover, infrastructure, paddock size, etc.), and (iii) vegetation functioning (magnitude and stability of primary productivity), in regions of A sia, A frica, A ustralia, and A merica. We collected data from global socioeconomic databases and remote sensing products for 4525 samples (representing uncultivated and cultivated conditions), located along 35 transects spanning semiarid to subhumid conditions. A Reciprocal Averaging ordination of uncultivated samples revealed a dominant gradient of declining woody cover accompanied by lower and less stable productivity. This gradient, likely capturing increasing vegetation degradation, had a negative relationship with poverty (characterized by infant mortality) and with market isolation (measured by travel time to large cities). With partial overlaps, regions displayed an increasing degradation ranking from A frica to S outh A merica, to A ustralia, to N orth A merica, and to A sia. A similar analysis of cultivated samples, showed a dominant gradient of increasing paddock size accompanied by decreasing primary productivity stability, which included all regions except A sia. This gradient was negatively associated with poverty and population density. A unique combination of small paddocks and high infrastructure differentiated A sian cultivated samples. While water availability gradients were related to productivity trends, they were unrelated to landscape pattern. Our comparative approach suggests that, in DST, human pressures have an overwhelming role driving landscape patterns and one shared with water availability shaping vegetation functioning.

A survey of dioxins (PCDDs and PCDFs) and dioxin-like PCBs in sheep and goat milk from Campania, Italy - M. Esposito; F.P. Serpe; S. Cavallo; R. Pellicanò; P. Gallo; G. Colarusso; R. D’ambrosio; L. Baldi; G. Iovane; L. Serpe (Food Additives & Contaminants Part B-Surveillance, 2010)

Three-Dimensional Mapping of Air Flow at an Urban Canyon Intersection - Matteo Carpentieri; Alan G. Robins; Sandro Baldi (Boundary-Layer Meteorology, 2009)

Differential composition of culture supernatants from wild-type Brucella abortus and its isogenic virB mutants - M. Victoria Delpino; Diego J. Comerci; Mary Ann Wagner; Michel Eschenbrenner; Cesar V. Mujer; Rodolfo A. Ugalde; Carlos A. Fossati; Pablo C. Baldi; Vito G. DelVecchio (Archives of Microbiology, 2009)

A hydrological onset and withdrawal index for the West African monsoon - G. A. Dalu; M. Gaetani; M. Baldi (Theoretical and Applied Climatology, 2009)

Climate Change: Causes and Medium Range Perspectives - G. Maracchi; M. Baldi (Veterinary Research Communications, 2006)

Cyclo-oxygenase-2 (COX-2) inhibition reduces apoptosis in acute myocardial infarction - A. Abbate; F. Limana; M. C. Capogrossi; D. Santini; G. G. L. Biondi-Zoccai; S. Scarpa; A. Germani; S. Straino; A. Severino; F. Vasaturo; M. Campioni; G. Liuzzo; et al. (Apoptosis, 2006)

Mechanisms of protection by pantoprazole against NSAID-induced gastric mucosal damage - M. Fornai; G. Natale; R. Colucci; M. Tuccori; G. Carazzina; L. Antonioli; S. Baldi; V. Lubrano; A. Abramo; C. Blandizzi; M. Del Tacca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Monte Carlo Inversion of DInSAR Data for Dislocation Modeling: Application to the 1997 Umbria-Marche Seismic Sequence (Central Italy) - S. Stramondo; S. Santini; P. Baldi; M. Dragoni; A. Piombo; S. Salvi; G. Spada (Pure and Applied Geophysics, 2004)

The climatology of sea breezes on Sardinia - M. Furberg; D. G. Steyn; M. Baldi (International Journal of Climatology, 2002)
Hourly wind speed and direction data from 12 coastline stations on Sardinia, Italy, are analysed in order to characterize sea breezes in the region. A set of criteria based on the diurnal reversal of wind direction, and the thermal gradient necessary to drive the circulation, is used to identify sea breeze days. Statistics are presented that describe the occurrence, duration, and strength of the sea breezes. On a stationwide basis, sea breezes are most frequent in the summer months (May–August), when they appear on more than one‐third of the days. Sea breeze occurrence and duration are the greatest for the stations on the east coast of the island. The all‐station average sea breeze duration reaches a maximum of about 9 h in June. The strength of the sea breezes is roughly 3 m s −1 during summer months on average over all stations in the sample. An analysis of mean daily hodographs for the stations in the sample shows clearly the onshore–offshore nature of the sea breeze circulation, and the response of the sea breezes to the local coastline. Sea breezes are shown to develop simultaneously on all coasts of the island under appropriate synoptic conditions. Copyright © 2002 Royal Meteorological Society.

Field assessments of gene flow from transgenic to cultivated rice (Oryza sativa L.) using a herbicide resistance gene as tracer marker - J. Messeguer; C. Fogher; E. Guiderdoni; V. Marfà; M. M. Català; G. Baldi; E. Melé (Theoretical and Applied Genetics, 2001)

Modeling coseismic displacements resulting from SAR interferometry and GPS measurements during the 1997 Umbria-Marche seismic sequence - S. Salvi; S. Stramondo; M. Cocco; M. Tesauro; I. Hunstad; M. Anzidei; P. Briole; P. Baldi; E. Sansosti; G. Fornaro; R. Lanari; F. Doumaz; et al. (Journal of Seismology, 2000)